Personal Selling Implementation and AIDA Model; Attention, Interest, Desire, Action - Leonard Adrie Manafe; Kori Pramita (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to determine consumer responses to the application of personal selling strategies applied by CV. Malcone in Sidoarjo, knowing the causes of consumers to make purchasing decisions, and knowing what actions are taken to keep consumers loyal to CV. Malcone. Design/methodology/approach: Qualitative methods and purposive sampling data collection techniques were used in this study and research data information was obtained from 8 (eight) informants who were consumers of CV. Malcone in Sidoarjo. Informants were selected according to certain criteria determined by the researcher. Findings: Research resulting that indicators of attention, interest, desire and action will be equipped the personal selling strategy. The guidelines for product marketing using the AIDA (Attention, Interest, Desire and Action) model which is in the personal selling process are applied by CV. Malcone Research limitations/implications: The majority of informants who met the criteria chose this product to be used as their outdoor equipment rental business. another limitation is that there is no implementation of personal selling strategies for potential customers who are in areas outside the island of Java. Practical implications: Several implications that can be applied in the strategy that has been implemented by CV. Malcone. Originality/value: The paper is original research. Paper type: Research paper